Removal of heavy metal from industrial wastewater by adsorption onto activated carbon prepared from fruit waste / Norhayati Talib … [et al.] - Talib, Norhayati; Alias, Nor Halaliza; Tengku Mohd, Tengku Amran; Md Zaki, Nurul Asyikin; Abu Bakar, Dr. Noor Fitrah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Activated carbon without a doubt has been the most popular and broadly used adsorbent in wastewater treatment throughout the world. This research will be conducted to produce the low cost alternatives activated carbon to adsorb heavy metal in waste water. Mangosteen and longan peels have been chosen as the source of the activated carbon due to its low cost, simple processing method, abundant in nature and it is a by product or waste material from fruit. The production of activated carbon was carried out by using chemical activation method. The activated carbons were characterized using Brunauer-Emmett-Teller (BET) and Fourier Transform Infrared (FTIR) Spectroscopy Analysis to analyse the ash, moisture content and surface functional group. Finally, the activated carbon adsorption activities were tested onto water containing heavy metal prepared in lab and industrial wastewater. The alternative source of the activated carbon from fruit waste provided a low cost treatment of heavy metal. It is a transformation towards a renewable energy source of waste treatment since the fruit waste used in this investigation are freely, abundantly and locally available. The resulting carbons are expected to be economically viable for wastewater treatment. Thus, it will promote the safer environment since the small scale industry will be afford to use the activated carbon for their waste water treatment rather than discharge the untreated heavy metal waste into the water source.